Novel method to quantify intracellular accumulation of polyphosphate in EBPR systems - Mesquita, D. P. (2013)
A new method for intracellular storage polyphosphate (poly-P)identification and quantification in enhanced biological phosphorus removal (EBPR) systems is proposed based on image analysis. In EBPR systems, 4',6-diamidino-2-phenylindole (DAPI) is usually combined with fluororescent in situ hybridization (FISH) to evaluate the microbial community. The proposed technique is based on an image analysis procedure specifically developed for determining poly-P inclusions within biomass suspension using solely DAPI by epifluorescence microscopy. Due to contradictory literature DAPI concentrations used for poly-P detection, the present work assessed the optimal DAPI concentration for samples acquired at the end of the EBPR aerobic stage when the accumulation is performed. Digital images were then acquired and processed by means of image processing and analysis. Regarding image analysis results and considering the current operational conditions, a promising correlation could be found between average poly-P intensity values and the analytical determination, although presenting a correlation coefficient somewhat far from the ideal. The proposed methodology can be seen as a promising alternative procedure to quantify intracellular poly-P accumulation in a faster and less labor intensive way.